Surface study of wood spindles, sanded along and against the wood grain, in woodturning. - Png, Cheong Keat (Nanyang Technological University, 2021)
This is a surface study on the roughness of wood cylinders subjected to two types of sequential sanding for finishing, that are common and unique to woodturning. Perpendicular sanding to the grain with rotating lathe and parallel sanding to the grain by manual effort on a static lathe. The unique and unequal conditions are a result of the constraints from the working and mounted orientation of the lathe and the workpiece respectively. Perpendicular cutting or sanding to the grain is known to yield rougher surfaces than cutting and sanding in the parallel direction. In this study, we found that both methods of sanding across three sample species (White Ash, Black Walnut, Angsana) with their respective advantages and disadvantages, unique and unequal when compared, were able to produce comparable surface roughness within the designed time constraint of the study. Skipping the coarsest sanding grit in the sequence when the initial surface quality to be sanded was satisfactory, was tested for its effects and the difference in surface quality was found to be imperceptible when compared with an equivalent. Surfaces were assessed primarily with the contact stylus profilometer along-the-grain. Qualitative assessment by sight and touch are conducted as well to determine if the measured differences in roughness on the surface are discernible to the human senses, which is of relevance to wood-based products, especially for fine wood furniture. A sub-study is done with a set of measurements collected with the laser confocal scanning microscope as another comparison. Across-the-grain and areal measurements from the LCSM data were also extracted for elementary comparison. A link could not be established between Along-the-grain and across-the-grain measurements as well as areal measurements in this study. Measurements across-the-grain on the cylindrical surface was found to be significantly higher than along the grain, in line with roughness studies on flat surfaces. There is no strong correlation between measurements across-the-grain and measurements along-the-grain. Surface based Sa, was found to have strong correlation with measurements across-the-grain.